2021
DOI: 10.1584/jpestics.d21-028
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and metabolism of pesticides in birds

Abstract: The median lethal dose of pesticide in acute oral toxicity, used as a conservative index in avian risk assessment, varies by the species with differences of less than one order of magnitude, depending on body size, feeding habit, and metabolic enzyme activity. The profiles of pesticide metabolism in birds with characteristic conjugations are basically common to those in mammals, but less information is available on their relevant enzymes. The higher toxicity of some pesticides in birds than in mammals is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 150 publications
(237 reference statements)
0
9
0
Order By: Relevance
“…Chlorpyriphos, an OP, inhibits acetyl choline esterase enzyme in a way that has cross generational implications (Anway et al, 2005) and it severely affects birds (Mitra et al, 2011). In order to monitor the pesticide residue in birds, the metabolic studies are required not only to identify the primary metabolites but also their accumulation and distribution within the body (Katagi and Fujisawa, 2021). Eng et al (2017) have reported the impairment of migration ability in white-crowned sparrow, a seed eating bird, after exposure to low (10% LD 50 ) and high dose (25% LD 50 ) of chlorpyriphos.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorpyriphos, an OP, inhibits acetyl choline esterase enzyme in a way that has cross generational implications (Anway et al, 2005) and it severely affects birds (Mitra et al, 2011). In order to monitor the pesticide residue in birds, the metabolic studies are required not only to identify the primary metabolites but also their accumulation and distribution within the body (Katagi and Fujisawa, 2021). Eng et al (2017) have reported the impairment of migration ability in white-crowned sparrow, a seed eating bird, after exposure to low (10% LD 50 ) and high dose (25% LD 50 ) of chlorpyriphos.…”
Section: Resultsmentioning
confidence: 99%
“…242 Additionally, the metabolic bioactivation of pesticides into more reactive compounds is another cause of avian toxicity. According to Katagi et al 's reviewed data on the bioactivation of pesticides in avian species, 243 several bioactivation pathway of pesticides produce higher avian toxicity, as summarized in Fig. 28.…”
Section: Structure-toxicity Relationship Analysis For Safer Chemical ...mentioning
confidence: 99%
“…Pollution threatens wildlife species all around the globe through a diversity of effects. At high enough concentrations, chemical pollution can be acutely toxic, causing direct mortality (Katagi & Fujisawa, 2021). At sub-lethal levels, pollutants may cause physiological harm both individually (Dietz et al, 2019), and when interacting with one another.…”
Section: Introductionmentioning
confidence: 99%